HDL cholesterol efflux does not predict cardiovascular risk in hemodialysis patients - Kopecky, Chantal; Genser, Bernd (Journal of the American Society of Nephrology, 2017)
The cardioprotective effect of HDL is thought to be largely determined by its cholesterol efflux capacity, which was shown to inversely correlate with atherosclerotic cardiovascular disease in populations with normal kidney function. Patients with ESRD suffer an exceptionally high cardiovascular risk not fully explained by traditional risk factors. Here, in a post hoc analysis in 1147 patients with type 2 diabetes mellitus on hemodialysis who participated in the German Diabetes Dialysis Study (4D Study), we investigated whether the HDL cholesterol efflux capacity is predictive for cardiovascular risk. Efflux capacity was quantified by incubating human macrophage foam cells with apoB-depleted serum. During a median follow-up of 4.1 years, 423 patients reached the combined primary end point (composite of cardiac death, nonfatal myocardial infarction, and stroke), 410 patients experienced cardiac events, and 561 patients died. Notably, in Cox regression analyses, we found no association of efflux capacity with the combined primary end point (hazard ratio [HR], 0.96; 95% confidence interval [95% CI], 0.88 to 1.06; P=0.42), cardiac events (HR, 0.92; 95% CI, 0.83 to 1.02; P=0.11), or all-cause mortality (HR, 0.96; 95% CI, 0.88 to 1.05; P=0.39). In conclusion, HDL cholesterol efflux capacity is not a prognostic cardiovascular risk marker in this cohort of patients with diabetes on hemodialysis.
Gesehen am 14.11.2018